Comparative HPLC-DAD-ESI-QTOF/MS/MS Analysis of Bioactive Phenolic Compounds Content in the Methanolic Extracts from Flowering Herbs of Monarda Species and Their Free Radical Scavenging and Antimicrobial Activities - Małgorzata Kozyra; Anna Biernasiuk; Magdalena Wiktor; Wirginia Kukula-Koch; Anna Malm (MDPI AG, 2023)
Comparative analysis of flavonoids and phenolic acids composition, in plants of six species of Monarda from family Lamiaceae was carried out. The 70% (v/v) methanolic extracts of flowering herbs of Monarda citriodora Cerv. ex Lag., Monarda bradburiana L.C. Beck, Monarda didyma L., Monarda media Willd., Monarda fistulosa L. and Monarda punctata L. were analyzed for their polyphenol composition as well as antioxidant capacity and antimicrobial effect. Liquid chromatography-electrospray ionization-tandem mass spectrometry (HPLC-DAD-ESI-QTOF/MS/MS) was used to identify phenolic compounds. The in vitro antioxidant activity was assessed using a DPPH radical scavenging assay, while antimicrobial activity was measured by the broth microdilution method allowing for MIC (minimal inhibitory concentration) determination. The total polyphenol content (TPC) was assayed by the Folin-Ciocalteu method. The results showed the presence of eighteen different components including phenolic acids and flavonoids together with their derivatives. The presence of six constituents (gallic acid, hydroxybenzoic acid glucoside, ferulic acid, p-coumaric acid, luteolin-7-glucoside and apigenin-7-glucoside) was found to be dependent on the species. To differentiate the samples, the antioxidant activity of 70% (v/v) methanolic extracts was studied and expressed as a percent of DPPH radical inhibition and in EC50 values (mg/mL). The latter values were as follows: M. media (EC50 = 0.090 mg/mL), M. didyma (EC50 = 0.114 mg/mL), M. citriodora (EC50 = 0.139 mg/mL), M. bradburiana (EC50 = 0.141 mg/mL), M. punctata (EC50 = 0.150 mg/mL) and M. fistulosa (EC50 = 0.164 mg/mL). Moreover, all extracts indicated bactericidal activity against reference Gram-positive (MIC = 0.07-1.25 mg/mL) and Gram-negative bacteria (MIC = 0.63-10 mg/mL) as well as fungicidal effect towards yeasts (MIC = 1.25-10 mg/mL). Staphylococcus epidermidis and Micrococcus luteus were the most sensitive to them. All extracts showed promising antioxidant properties and noteworthy activity against the reference Gram-positive bacteria. Antimicrobial effect of the extracts against the reference Gram-negative bacteria as well as fungi (yeasts) from Candida spp. was slight. All extracts showed bactericidal and fungicidal effect. The obtained results indicated that the investigated extracts from Monarda spp. could be potential sources of natural antioxidants and antimicrobial agents, especially with activity towards Gram-positive bacteria. The differences in the composition and properties of the studied samples may influence the pharmacological effects of the studied species.